2013
DOI: 10.1183/09031936.00167713
|View full text |Cite
|
Sign up to set email alerts
|

Exercise oxygen uptake efficiency slope independently predicts poor outcome in pulmonary arterial hypertension

Abstract: 7Borghi-Silva A, Carrascosa C, Oliveira CC, et al. Effects of respiratory muscle unloading on leg muscle oxygenation and blood volume during high-intensity exercise in chronic heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 12 publications
3
22
0
Order By: Relevance
“…9,[10][11][12][13][14][15] Recently, a few studies reported on the OUES as a prognostic marker in patients with cardiopulmonary diseases. [16][17][18][19][20][21] A more established exercise parameter to predict prognosis is the VE/VCO 2 slope, which represents the linear regression relation of VE and carbon dioxide production (VCO 2 ). 22 It is a measure of ventilatory efficiency that has been shown to be related to morbidity and mortality in various groups of patients, such as patients with chronic heart failure (CHF), congenital heart disease, chest pain suspected to be CAD and respiratory disease.…”
Section: Introductionmentioning
confidence: 99%
“…9,[10][11][12][13][14][15] Recently, a few studies reported on the OUES as a prognostic marker in patients with cardiopulmonary diseases. [16][17][18][19][20][21] A more established exercise parameter to predict prognosis is the VE/VCO 2 slope, which represents the linear regression relation of VE and carbon dioxide production (VCO 2 ). 22 It is a measure of ventilatory efficiency that has been shown to be related to morbidity and mortality in various groups of patients, such as patients with chronic heart failure (CHF), congenital heart disease, chest pain suspected to be CAD and respiratory disease.…”
Section: Introductionmentioning
confidence: 99%
“…The units L/min/log(L/min) [25][26][27][28][29][30][31] , L/min/logL [32][33][34][35] and L/ min/logVE 36) are not logical, because logarithm is not included in the unit.…”
Section: The Unit Of Ouesmentioning
confidence: 99%
“…The OUES has been applied to evaluate cardiorespiratory fitness in patients with various diseases as well as in healthy individuals 1,3,4,9,11,15,17, [24][25][26][32][33][34][35]37,44) ; these various diseases include heart diseases 1,4,6,8,9,12-16,18, 21,28,29,33,38,[40][41][42][43][44]46) , orthopedic surgery 5) , gastroenterological surgery 7) , intellectually disabled young people 10) , multiple sclerosis 17, 23,33,39,45) , chronic obstructive pulmonary disease 15,27,33,45) , pulmonary arterial hypertension 19,20,30,36) , lung cancer 22) , severely overweight people 31,32) and cystic fibrosis 34,35) . Despite the high concern regarding the value of OUES, its unit is still unsettled.…”
Section: Introductionmentioning
confidence: 99%
“…It can be used as an estimate of peak VO 2 which requires only submaximal effort [121,122]. It has recently been shown to be of prognostic value in PAH [123].…”
Section: Cardiopulmonary Exercise Testingmentioning
confidence: 99%